2021
DOI: 10.12659/msm.934161
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Predictive Role of Oxidative Stress Genes in the Prognosis of Glioma Patients

Abstract: Background Gliomas are primary aggressive brain tumors with poor prognoses. Oxidative stress plays a crucial role in the tumorigenesis and drug resistance of gliomas. The aim of the present study was to use integrated bioinformatics analyses to evaluate the prognostic value of oxidative stress-related genes (OSRGs) in glioma. Material/Methods Disease- and prognosis-associated OSRGs were identified using microarray and clinical data from the Chinese Glioma Genome Atlas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Acquisition of OSRGs. The OSRGs were searched on the online GSEA website (http://www.gsea-msigdb.org/gsea/ index.jsp) [12]. The input keywords included oxidative stress and the 32 gene sets related to oxidative stress.…”
Section: Methodsmentioning
confidence: 99%
“…Acquisition of OSRGs. The OSRGs were searched on the online GSEA website (http://www.gsea-msigdb.org/gsea/ index.jsp) [12]. The input keywords included oxidative stress and the 32 gene sets related to oxidative stress.…”
Section: Methodsmentioning
confidence: 99%
“…From The Cancer Genome Atlas (TCGA) website, we downloaded RNA-Seq data and clinicopathological information of 587 UCEC samples, containing 35 normal samples and 552 tumor samples ( , accessed on 10 July 2022). The OSRGs (n = 666) were obtained from the online GSEA website ( , accessed on 10 July 2022) [ 23 ]. A total of 548 patients with UCEC were included in the analysis after downloading the corresponding clinical and survival information from the TCGA cohort.…”
Section: Methodsmentioning
confidence: 99%
“…And the impaired autophagy was involved in IPF pathogenesis [9][10][11][12][13] . Fascinatingly, the prevailing literatures autophagy suggested that impaired autophagy/mitophagy was also involved in keloids [14][15][16][17] . Therefore, the oxidative stress may also play an important role in keloids, which still remains unclear.…”
Section: Introductionmentioning
confidence: 99%